Mind-Body Practices in Integrative Medicine - Walach, Harald (Religions, 2012)
Mind-Body practices have become increasingly popular as components of psychotherapeutic and behavior medicine interventions. They comprise an array of different methods and techniques that use some sort of mental-behavioral training and involve the modulation of states of consciousness in order to influence bodily processes towards greater health, well-being and better functioning. Mind-body practices may thus be interpreted as the salutogenetic mirror image of psychosomatic medicine, where psychophysiological and health consequences of specific psychological states are studied, such as stress arousal, psychological trauma or depression. This contribution examines the empirical evidence of the most common mind-body techniques with regard to their salutogenetic potential. We concisely discuss some aspects of the mind-body problem, before we consider some historical aspects and achievements of psychosomatic medicine. We then turn to some prominent mind-body practices and their application, as well as the empirical database for them.